Karakteristik dan Konsep Pendidikan Islam yang Terkandung dalam Surah Al-A’raf Ayat 179 - Surawardi Surawardi (Transformatif, 2017)
The problem in this research is how the concept of Islamic Education contained in Surah Al-Araf Verse 179. The aim of this study was to determine the concept of Islamic Education contained in Surah Al-Araf Verse 179. In Surah Al-Araf verse 179, Allah describes bahwasannya who will be the inhabitants of hell are people neglect and do not use their sense their minds to understand the true nature of things, is unwilling to avail their eyes and ears either to conclude all who knew and took the sciences as well as to know the signs of God that is in his creation, and the signs of his greatness contained in his books that are both a cause and the perfection of faith into the soul urge to enhance one's Islam. Islamic educational values contained in Surah Al-Araf verse 179 includes: Hell Hell supplied For Jin and Man, people who have a sense / brain, people who have eyes, those who have ears, diumpakan like stars even worse again. Karakteristik dan Konsep Pendidikan Islam yang Terkandung dalam Surah Al-A’raf Ayat 179